Conversion of waste shipping oil into diesel-like oil via microwave-assisted pyrolysis. Issue 6 (December 2017) - Wan Mahari, Wan Adibah; Zainuddin, Nur Fatihah; Chong, Cheng Tung; Lee, Chern Leing; Lam, Wei Haur; Poh, Seng Chee; Lam, Su Shiung
Highlights: Waste shipping oil is pyrolyzed via a microwave-heated bed of activated carbon. Activated carbon bed provides fast heating and good pyrolysis cracking capacity. Oil product is diesel-like, free of sulphur, low in oxygen and nitrogen. Viscosity of oil product is comparable to the viscosity of diesel fuel. Pyrolysis oil shows potential as a cleaner and sustainable fuel source. Abstract: Waste shipping oil, a mixture of used lubricating oil and seawater derived from ship engine operation, was tested for its potential to be converted into a fuel product via an innovative microwave-assisted pyrolysis approach using a reaction bed of activated carbon. Higher carbon to waste ratio was found to have beneficial effects in promoting pyrolysis cracking to produce a higher yield of pyrolysis oil, recording a yield of up to 66 wt%. The pyrolysis oil comprised of aliphatic hydrocarbons (C5 –C15 hydrocarbons) that are within the hydrocarbon range for gasoline and diesel. Combined with the detection of low viscosity (2 − 5 mm 2 /s) and high calorific value (46 MJ/kg) nearly comparable to diesel, the pyrolysis oil shows potential to be upgraded to diesel fuel. The oil product was also detected to have low contents of oxygen (0.1 wt%) and sulphur (0.02 wt%), showing promising features as a 'cleaner' fuel source with potentially reduced formation of tar (an oxygenated byproduct) and low emission of SOx during the use of the oil as fuel in combustion process. Our results indicate that microwave-assisted pyrolysis shows potential as an alternative to transform waste shipping oil into an alternative fuel source.